Race, Racism and Administrative Callousness: Using Critical Race Theory for a Race-Conscious Public Administration. (3rd September 2021) - Blessett, Brandi; Gaynor, Tia Sherèe
Abstract: This special symposium examines CRT across public and nonprofit spaces to better understand the effects of denying race and racism within the spaces they govern. Although ever present across public administration and nonprofit institutions, explicit discussions and/or initiatives designed to address racism, at the root level, are rare. While an increasingly growing area of interest, the study of public administration continues to avoid explicit conversations capable of leading to institutional shifts in racial justice. The articles included within this symposium move the study of racism (as a system of oppression) by using critical race theory (as a tool to eradicate this unjust system) within the field forward. Each manuscript offers critical race theory as a tool for public administration to move beyond its traditional notions of neutrality, objectivity, and technical rationality into a discipline and practice that accurately contextualizes history, centers the lived experience, and values racial justice as worthy of prioritization and action.